TANGGAPAN PENGUNJUNG TERHADAP FASILITAS OBYEK WISATA MASJID AGUNG MADANI ISLAMIC CENTRE PASIR PENGARAIAN ROKAN HULU - Salsa Azzahra; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The facilities of tourist attraction gives many visits opportunity because it is needed by visitors. A tourist attraction should pay attention, maintan an develop to the facilities of tourist attraction and it can be able to increase the number of tourism visitors. The aim of this research was to find out how tourist responses about the facilities of tourist attraction of The Great Mosque Madani Islamic Centre of Pasir Pengaraian Rokan Hulu. This research used quantitative descriptive method by analyzing the issues are raised. The sample of this research is 100 samples by using slovin formula. To collect the data, the researcher used questionaire, observation, documentation and interview. To measure the data, the researcher used likert scale tp know the long-short of interval. Based on the result of this research, the responses of visitors about the facilities of tourist attraction of the Great Mosque Madani Islamic Centre of Pasir Pengaraian Rokan Hulu by sub variables are main facilities, second facilities and supporting facilities. All of the whole responses of visitors about the facilities of tourist attraction of the Great Mosque Madani Islamic Centre of Pasir Pengaraian Rokan Hulu from each aspect is included very good category. Keywords : The Facilities of Tourist Attraction, Great Mosque